Mandatory audit firm and audit partner rotation - Abdul Rasid, Siti Zaleha (2014)
Mandatory audit partner and audit firm rotation are important part of audit quality component. Some regulators and scholars believe that auditor rotation shows auditor’s independence in the audit context. In order to achieve high audit quality, most of the researchers agree on as a result of auditor rotation, the financial reporting and the audit quality will be enhanced owing to auditor’s independence. This study reviews the recent years with respect to audit partner rotation, the audit firm rotation and audit quality as well as recognizing overlook in the literature where future studies are needed to be done. Based on recent studies, both audit firm and audit partner rotation enhance and improve audit quality, as high audit quality increases the transparency of financial reporting.